INNOVATIVE REGULATORY-CONFORMING BIOANALYTICAL APPROACHES ENABLING SYSTEMATIC INVESTIGATIONS OF PHARMACOKINETICS AND PHARMACODYNAMICS BY PAEDIATRIC CLINICAL STUDIES IN ALL AGE GROUPS. Issue 1 (14th December 2015) - Burckhardt, Björn B; Tins, Jutta; Läer, Stephanie
Abstract : Background: Clinical investigations on pharmacokinetics and pharmacodynamics are highly required to improve paediatric pharmacotherapy. Especially in neonates and infants the conduct is challenging due to e.g. high ethical and analytical burdens. The trial-related blood lost should not exceed 3% of the total blood volume within 4 weeks (1). Appropriate assays are lacking which leads to the fact that many drugs are not sufficiently investigated in small children. Objective: Development of a tailored comprehensive bioanalytical setting for pharmacokinetic and pharmacodynamic investigations of drugs acting on the RAA system in neonates up to adolescents. Methods: Bioanalytical HPLC-MS/MS methods for invasive and non-invasive determination of pharmacokinetics of aliskiren and enalapril in 50–100 µL serum, urine, and saliva were developed. Changes of humoral parameters of the RAA system were measured by five immunological assays in a total volume of 2.1 mL. All assays were scaled up to a high throughput approaches to meeting clinical demands. The applicability of the low-volume assays was assessed by a proof-of-concept study in 22 healthy volunteers and a regulatory-compliant Phase I study. Results: The conducted studies using the low-volume assays revealed comparable pharmacokinetic results of aliskiren and enalapril in serum and urine when compared to literature. Changes in the humoral parameters are also similar and prove the applicability of the bioanalytical platform. Very dense and reliable individual concentration-time profiles of the drugs and the humoral parameters over 192 h were obtained in 45 mL blood only. Saliva appeared inappropriate to replace invasive pharmacokinetic sampling. Conclusion: The child-appropriate bioanalytical platform can be applied in upcoming paediatric Phase II and Phase III studies of the LENA (Labeling of Enalapril from Neonates up to Adolescents) project. Meaningful concentration-time profiles with 6–7 sampling points can be obtained even in neonates without infringing ethical recommendations on trial-related blood lost. The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA).